Quality of life of fitness professionals in Portugal: Comparative and correlation study - Vieira, Isabel; Esteves, Dulce; Ramos, Liliana; Simões, Vera; Franco, Susana (Frontiers in Psychology, 2022)
Fitness has been revealing a positive impact on the quality of life of practitioners and fitness professionals represent a role model for their customers in the fitness industry, emphasizing the need to know their quality of life indices. The purpose of this study is to characterize the quality of life of fitness professionals in Portugal, compare it between groups and correlate quality of life with sociodemographic and work-related variables. A total of 388 fitness professionals answered an online survey about sociodemographic and work-related variables and the Portuguese version of the World Health Organization Bref Quality of Life Assessment. Descriptive analysis, t-test, ANOVA, Kruskal-Wallis, Pearson and Spearman were used for statistical analysis. The results suggest that fitness professionals in Portugal have different levels of quality of life, considering the high standard deviation, with lower average indices than other countries. The lowest scores of quality of life were verified in the environment domain. The results of the comparison between groups suggest that being male, married and having a master’s degree or higher were the characteristics with better indices of quality of life. Age, professional experience and net salary reveal a positive relation/association with quality of life. Body&mind group classes per week, maximal group classes per day, paid and unpaid working hours per week and annual expenses related to the profession reveal a negative relation/association. Maximal group classes per day results could be an important finding to help minimize the physical problems among fitness professionals and body&mind group classes per week results could be an indicator of the fitness professionals’ adaptation that allows them to remain on the profession. Unpaid working hours per week has the highest number of significant relations/associations with quality of life. These findings could be important to improve the quality of life of fitness professionals. Thus, they could result in better work capacity and, therefore, fewer professionals would abandon the profession. It would also have a positive impact on the fitness industry and on the promotion of physical activity for a healthier society. More research is needed regarding the quality of life of fitness professionals.